Uterine Rupture after Laparoscopic Myomectomy in Two Cases: Real Complication or Malpractice? - Antonella Vimercati; Vittoria Del Vecchio; Annarosa Chincoli; Antonio Malvasi; Ettore Cicinelli (Case Reports in Obstetrics and Gynecology)
We describe two cases of uterine rupture in pregnancy after laparoscopic myomectomy and analyze all the aetiological factors involved in this circumstance according to the recent literature, focusing above all on the surgical procedures and the characteristics of the excised myomas. The two cases of uterine rupture in pregnancy following laparoscopic myomectomy occurred at 36 and 18 weeks of gestation, respectively. Both women had undergone laparoscopic multiple myomectomy and uterine rupture occurred along the isthmic myomectomy scars, despite the fact that compliance with all the recent technical surgical recommendations for the previous laparoscopic multiple myomectomy had been fully observed. In our cases we identified the isthmic localization, size of the excised myomas (≥4 cm), and individual characteristics of the healing process as possible risk factors for “a real complication.” Larger studies and robust case-control analyses are needed to draw reliable conclusions; special care should be paid when performing laparoscopic myomectomy in women planning a later pregnancy.